Penambahan Tepung Ubi Ungu (Ipomea batatas L.) Terhadap Sifat Organoleptik dan Kimia dalam Pembuatan Pizza - Andra Tersiana Wati; Ertha Martha Intani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Purple sweet potato flour (Ipomea batatas L.) can be developed as a partial substitute in processing wheat flour-based food products such as pizza. Pizza has a thin round shape with the addition of various toppings on it. This study aims to determine the effect of adding purple sweet potato flour in pizza making on the organoleptic and chemical characteristics of the resulting pizza product. There were 6 variations of pizza with purple sweet potato flour substitution concentration of 0%, 10%, 20%, 30%, 40% and 50%. This study used a completely randomized design method with two repetitions. The resulting pizzas were tested sensory including preference tests as well as differentiation tests (sweet potato flavor, sweet potato aroma, dark purple color, and soft texture). Furthermore, the selected pizzas were analyzed chemically, including proximate analysis and antioxidant activity. Based on statistical tests showed that the addition of purple sweet potato flour was quite favorable at a concentration of 30% with a water content of 44.45%, ash content of 3.48 (% db), protein content 10.26 (%db), carbohydrate content 74.89 (%db) with energy 239.58 (cal/100 g) and antioxidant activity (RSA) 71.26%. Keywords: antioxidant activity, pizza, purple sweat potato flour, purple sweat potato, sensory test